Study of Vessel Conditions in Different Categories of Weight for Early-Stage of Deep Vein Thrombosis (DVT) Diagnosis - Mat Harun, Noor Hafizzatul ‘Izzah bt; Ibrahim, Nabilah bt; Wan Zakaria, Wan Nurshazwani bt; Nik Fuad, Nik Farhan bin; Aziz, Nur Shazilah bt (International Journal of Integrated Engineering, 2015)
In this paper, the clinical experiment study is presented to diagnose the Deep Vein Thrombosis (DVT). The diagnosis of DVT is commonly used by monitoring the blood velocity and the present of thrombus in vessel from B-mode ultrasound image associated with the application of Doppler ultrasound. However, the monitoring of those parameters will only be confirmed when someone had already suffered from DVT disease. Thus, this study is to diagnose the early stage of DVT. Since it is difficult to recognize the vessel condition at the early stage of DVT, the evaluation of vein mechanism based on different categories of weight at the early stage of DVT is proposed. The wall displacement and blood flow velocity is considered to be the important parameters to construct a clinical model of DVT risk factor, thereby constitutes an important contribution for predicting probability of Deep Vein Thrombosis (DVT).